Pengaruh Kepemimpinan Kepala Sekolah dan Disiplin Guru terhadap Kinerja Guru di Sekolah Dasar Kecamatan Lempuing Jaya Ogan Komering Ilir - Tatik Lestari; Nur Ahyani; Djunaidi Djunaidi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The aim of this research is to describe and analyze. 1). To describe and analyze the influence of the principal's leadership on teacher performance at the Lempuing Jaya elementary school, Ogan Komering Ilir. 2). to describe and analyze teacher discipline on teacher performance in elementary schools located in Lempuing Jaya, Ogan Komering Ilir. 3). To describe and analyze the influence of principal leadership and teacher discipline on teacher performance at Lempuing Jaya elementary school, Ogan Komering Ilir. This research explains the important role of effective school leadership in fostering an environment conducive to high teacher performance. It emphasizes that teacher discipline, defined as compliance with established regulations and commitment to professional responsibility, significantly impacts an educator's overall effectiveness. The methodology used was quantitative, correlational research type with a total of 265 people for drawing research samples using proportional random sampling, so that a sample of 73 respondents was obtained. Data collection techniques use documentation and questionnaires. The data analysis technique uses the t test. The results of this research indicate that the principal's leadership style and discipline among teachers are very important in improving teacher performance results in elementary schools in Lempuing Jaya Ogan Komering Ilir subdistrict.